Natural-based biomaterial for skin wound healing (gelatin vs. collagen): expert review - Naomi, Ruth; Bahari, Hasnah; Muhd Ridzuan, Pauzi; Othman, Fezah (MDPI, 2021)
Collagen (Col) and gelatin are most extensively used in various fields, particularly in pharmaceuticals and therapeutics. Numerous researchers have proven that they are highly biocompatible to human tissues, exhibit low antigenicity and are easy to degrade. Despite their different sources both Col and gelatin have almost the same effects when it comes to wound healing mechanisms. Considering this, the bioactivity and biological effects of both Col and gelatin have been, and are being, constantly investigated through in vitro and in vivo assays to obtain maximum outcomes in the future. With regard to their proven nutritional values as sources of protein, Col and gelatin products exert various possible biological activities on cells in the extracellular matrix (ECM). In addition, a vast number of novel Col and gelatin applications have been discovered. This review compared Col and gelatin in terms of their structures, sources of derivatives, physicochemical properties, results of in vitro and in vivo studies, their roles in wound healing and the current challenges in wound healing. Thus, this review provides the current insights and the latest discoveries on both Col and gelatin in their wound healing mechanisms.